Investigating Chlamydomonas reinhardtii as a functional food and feed ingredient - Darwish, Randa (2018)
Microalgae have become recognized as excellent sources for many valuable nutrients. Chlamydomonas reinhardtii is a green microalga which has attracted attention as a model organism for recombinant protein and vaccine production, but its nutritional value and key functional components have not been previously assessed. Initial comparisons with species already used in this manner (Chlorella and Spirulina) indicated that microalga had potential to be added as a nutritional addition to food. C. reinhardtii was characterised by a high omega 3 fatty acids content and a good source of pigments (chlorophyll (a+b), β-carotene (provitamin A) and lutein). In-vitro digestion trials were conducted to determine the concentrations of digestive enzymes (pepsin and pancreatin) released from cells. The digestive conditions caused major changes in structure, cell shape and partially unlocked nutrients from the cells. Grinding C. reinhardtii with liquid nitrogen increased accessibility of β-carotene from 6% for intact cells to 14%, iron from 4.04% to 8.8% and inclusion of PLRP2 significantly improved lipid hydrolysis. Determining growth and other significant parameters for zebrafish fed with C. reinhardtii revealed a significant improvement when compared with zebrafish consuming a standard fish diet. Interestingly, fish on a diet containing C. reinhardtii was characterised by a significantly higher linolenic acid (C18:3 n-3) content (P≤ 0.05). Inclusion of the fatty acid hexadecatrienoic acid (C16: 4-n-3) ensured that C. reinhardtii lipid was hydrolysed and absorbed in the zebrafish intestine. A visible yellow pigmentation of zebrafish (egg in the female and skin in the male) fed with C. reinhardtii was distinct from the control, this yellow pigmentation was determined to be lutein which the zebrafish had assimilated from C. reinhardtii cells. There was a significant increase in retinol in C. reinhardtii fed fish (10 and 20%) when compared to the control. Thus, it is deducted that zebrafish was able to assimilate β-carotene and convert it to vitamin A. All things considered, C. reinhardtii displayed a great potential as a functional food and feed ingredient which is characterized by relatively good digestibility both in vivo and in vitro.